Evaluation of Staresmet® for Rapid Detection of Methicillin Resistance in Clinical Isolates of Staphylococcus Aureus - Soysal, M.; Çoban, A.Y. (AVES Ibrahim Kara 105/9 Buyukdere Cad Mecidiyekoy,Sisli, Istanbul 34394, 2017)
Objective: The aim of this study is evaluation of StaResMet® (AYCMED Medikal ve Tıbbi Cihazlar San. ve Tic. A.Ş., Samsun, Turkey) as a new colorimetric test kit for rapid detection of the methicillin resistance in Staphylococcus aureus isolates. Methods: Methicillin resistance was determined by the microdilution method according to Clinical & Laboratory Standards Institute (CLSI) recommendations. The StaResMet® kit and VITEK® 2 Compact (bioMérieux, Marcy l’Etoile, France) automated system were used according to the recommendations of the manufacturers. The broth microdilution test was considered as reference method for the comparison of the tests. S. aureus ATCC 29213 (methicillin-susceptible) and ATCC 43300 (methicillin-resistant) were used as quality control strains. Isolates were accepted as resistant to methicillin if they had a cefoxitin minimum inhibitory concentration of ≥8 μg/ml according to the CLSI criteria. Results: It was found that out of 277 isolates, 118 S. aureus isolates were methicillin-resistant and 159 were susceptible to methicillin. It was determined that 118 S. aureus isolates were resistant to methicillin by the broth microdilution method, VITEK® 2 Compact and StasResMet® kits. 159 isolates were susceptible to methicillin by three methods. According to these results, specificity, sensitivity, positive and negative predictive values of StaResMet® kit were 100%. Conclusions: StaResMet® kit has a potential use for rapid detection of methicillin-resistant S. aureus (MRSA). © 2017, AVES Ibrahim Kara. All rights reserved.
Staphylococcus Aureus İzolatlarında Metisilin Direncinin Hızlı Tespitinde Staresmet®’in Değerlendirilmesi
Keywords: Methicillin Resistance; Staphylococcus Aureus; Staresmet® Kit